NEXT-GEN LOGISTIC MANAGEMENT: RANCANG BANGUN SISTEM DENGAN LARAVEL DAN MYSQL - Mega Wahyu Rhamadani; Abdullah Ardi (Jurnal Teknoinfo, 2025)
In the increasingly complex and competitive logistics industry, optimizing freight management is crucial for enhancing operational efficiency. This study develops a web-based freight management system utilizing the Laravel framework and MySQL database, aiming to improve operational effectiveness at PT. Tunas Mendayung Group. The system development follows the Waterfall methodology, encompassing requirements analysis, system design, implementation, and testing phases. System evaluation was conducted through black-box testing, achieving an average success rate of 98.6%, with authentication accuracy of 100% for administrators and 98% for users, CRUD operations at 95%, shipment status validation at 100%, and pricing evaluation accuracy at 97%. The system demonstrated an average response time of 2 seconds and full compatibility across major web browsers. The primary contribution of this research lies in the development of an integrated freight management system that not only incorporates real-time shipment tracking and robust authentication mechanisms but also optimizes data processing efficiency through a modular architecture that is adaptable to logistics industry demands. Unlike previous studies that primarily focused on data optimization without considering interactive user features, this system offers a comprehensive solution that enhances operational transparency and the accuracy of shipment information. Consequently, the proposed system has the potential to serve as a model for logistics companies seeking to adopt web-based technologies to improve competitiveness and overall industry efficiency.